Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species - Alavi, Jalil; Minaei, Kambiz (Zootaxa, 2018)
An illustrated key is provided to 27 species of Aeolothrips Haliday recorded from Iran, including two new species: A. persiae sp. n. from Chenopodium album [Chenopodiaceae] and A. tatari sp. n. from Sinapis arvensis [Brassicaceae]. Variation among populations of A. tenuicornis from Iran, Europe and Mediterranean area is discussed. A. neyrizi is synonymized with A. flaviventer. An update checklist of Iranian Aeolothrips is provided.